Topical for Postoperative Wound Healing: A Prospective Randomized Controlled Trial - Joshua T. Chew BEng(Hons), MD; Joshua J. Xu MD, MSc; Thomas A. J. Goff MBCHb, FRCS; Karen A. Fogarty MN, MAHP; Michael J. Symes BPhysio(Hons), MBBS(Hons), MPH, FRACS, FAOrthA; Brahman S. Sivakumar MBBS, BSci(Med), MS, MSc, FRACS, FAOrthA, PFET; Andrew P. Wines MBBS, FRACS, FAOrthA (Foot & Ankle Orthopaedics)
Background: Numerous ointments may be applied to surgical incisions in the postoperative period to minimize scar formation. There is little evidence assessing their efficacy on wound healing following foot and ankle procedures. This trial was conducted to assess the efficacy of Bixa orellana (Urucu) ointment in the treatment of postoperative elective foot and ankle incisions, compared with conventional postoperative wound care using a control ointment. Methods: A prospective, single-center, randomized controlled trial of adults who had undergone elective foot and ankle surgery was performed. Participants were randomized into receiving either a protocol of B orellana ointment application or conventional postoperative wound care with a control ointment. These ointments were applied 2 weeks postoperatively for a 4-week duration. The primary outcome assessed was the Patient and Observer Scar Assessment Scale (POSAS) 6 weeks postoperatively. Results: Significant improvements were noted in observer-reported wound vascularity, pigmentation, thickness, relief, pliability, and surface area with the use of Urucu, when compared to the control ointment. Overall, observers reported that scars treated with Urucu cream were found to more closely resemble normal skin with an overall POSAS score of 2.56 compared with 3.33 for the control ointment ( P  < .01). Lower scores in this instance indicate a more favorable result. Similarly, patients also reported a similar finding with an overall POSAS score of 3.70 for Urucu compared with a control ointment, 4.80 ( P  = .012). No difference was noted in terms of antibiotic use, delayed wound healing, or return to theatre. Two patients had adverse effects on the application of Urucu ointment in the form of a localized reaction and pruritis that improved with treatment cessation ( P  = .08). Neither patient required any further intervention. Conclusion: Topical Urucu ointment demonstrated promising early improvements in POSAS scores from both patients and observers, particularly in pigmentation and pliability domains, but findings should be interpreted cautiously because of the small sample size and short follow-up. Level of Evidence: Level I, randomized controlled trial.